Analisis Daya Gabung Galur-Galur Jagung Tropis di Dua Lokasi - Yustiana, ,; Syukur, Muhamad; Sutjahjo, Surjono Hadi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
The objective of this research was to analyze the combining ability of nine tropical maize lines from PT. BISI International, Tbk’s collections across two locations. The research used a complete diallel mating design according to Griffing’s method 1. Randomized completely block design was used as an experimental design with three replications in each location, Kediri and Nganjuk, East Java. Result of the combining ability analysis revealed that location effect was significant for all traits. Additive gene effects were more important in controlling plant height, ear length, ear diameter and 1,000-grain weight while non-additive gene effects were more important in controlling days to harvest, ear weight per plot and yield potency. Good combiners across locations for days to harvest were Sr-1#247 and Sr-1#086. Sr-1#001 and Loe#187; Pron#077 and Loe#057; Pron#142 and Loe#187; Loe#187 and Loe#057; Sr-1#001 and Loe#187 were a good combiners for ear length, ear diameter, 1,000-grain weight, ear weight per plot and yield potency, respectively. Best specific combinations for several important traits were generated from parent lines with high x low GCA. Sr-1#001xLoe#055; Loe#187xLoe#055 and Loe#057xLoe#055 were the best for ear weight per plot and yield potency.Keywords: combining ability, diallel, G x E interaction, tropical maize